Analysis of Prognostic Alternative Splicing Reveals the Landscape of Immune Microenvironment in Thyroid Cancer - Wu, Jian; Sun, Yifang; Li, Junzheng; Ai, Maomao; You, Lihua; Shi, Jianbo; Yu, Feng (Frontiers in Oncology, 2021)
Background: The incidence of thyroid cancer(THCA) continues to rise in recent decades. More and more evidence showed that the unbalanced alternative splicing (AS) promoted the occurrence of cancers and leads to poor prognosis. However, the research on alternative splicing events in THCA was still lacking and its underlying mechanism was not fully understood. Our goal was to identify a novel prognostic signature based on AS events and to reveal its relationship with tumor microenvironment. Methods: Based on AS data, transcriptional data and clinical information, differentially expressed alternative splicings (DEASs) were screened out. Lasso regression and multi-Cox regression were employed to identify prognostic related AS events and established prognostic signature. The predictive ability of predictive signature was assessed by Kaplan-Meier(K-M) survival curve, risk plots and receiver operating characteristic (ROC) curves. For further research, correlations between tumor infiltrating immune cells, immune checkpoints, immune score and prognostic signature were analyzed. Results: According to lasso regression, a total of 5 AS events were selected for constructing the signature. K-M survival curve showed that the higher the risk score, the worse the OS of the patients. Risk plots further confirmed this view. ROC curves indicated the high predictive efficiency of the prognostic signature. As for tumor immune microenvironment, patients in the high risk group had a higher proportion of immune cells, including plasma cell, CD8+ T cell, Macrophages (M0 and M2) and activated dendritic cell. Immune checkpoints, such as PDCD1LG2, HAVCR2, CD274, etc, were significantly higher in high risk group. We also found that the ESTIMATE score, stromal score and immune score were lower in the high risk group, while the result of tumor purity was contrary. Conclusions: Collectively, a prognostic signature consisted of 5 AS events in THCA was established. Furthermore, there was a inextricable correlation between immune cell infiltrating, immune checkpoints and AS events. This result is of far-reaching significance and provide basis for THCA immunotherapy in the future.